2021
DOI: 10.3390/biom11020203
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of LncRNA WT1-AS/miR-206/NAMPT Axis as Prognostic Biomarkers in Lung Adenocarcinoma

Abstract: Lung cancer is the world’s highest morbidity and mortality of malignant tumors, with lung adenocarcinoma (LUAD) as a major subtype. The competitive endogenous RNA (ceRNA) regulative network provides opportunities to understand the relationships among different molecules, as well as the regulative mechanisms among them in order to investigate the whole transcriptome landscape in cancer pathology. We designed this work to explore the role of a key oncogene, MYC, in the pathogenesis of LUAD, and this study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The functions of long non-coding RNAs (lncRNAs) have been proved in protecting chromosome integrity, maintaining genome structure, transcription, translation and epigenetic regulation [ 8 , 9 , 10 ]. Imbalances of lncRNA are also associated with the development of many diseases and complications, such as premature preterm rupture of membrane, autism spectrum disorders, and cancer [ 11 , 12 , 13 , 14 ]. MicroRNAs (miRNAs) target and induce translation inhibition or degradation of mRNA to control gene expression and regulate biological processes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of long non-coding RNAs (lncRNAs) have been proved in protecting chromosome integrity, maintaining genome structure, transcription, translation and epigenetic regulation [ 8 , 9 , 10 ]. Imbalances of lncRNA are also associated with the development of many diseases and complications, such as premature preterm rupture of membrane, autism spectrum disorders, and cancer [ 11 , 12 , 13 , 14 ]. MicroRNAs (miRNAs) target and induce translation inhibition or degradation of mRNA to control gene expression and regulate biological processes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results do not report NAMPT in BALF samples; rather, it is detected only in serum, evidencing a lower abundance in LC-IPF with respect to IPF and CTRLs. NAMPT is frequently studied in lung cancer, particularly in NSCLC, and it is considered a potential target of treatment [ 73 , 74 ], as well as a prognostic biomarker [ 75 ]. Its characteristic low abundance in serum samples of LC-IPF patients could be tested in a wider cohort of samples in order to render our data more robust.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA (WT1-AS)–miRNA (mir-200a-3p)–mRNA (IGF2BP2) regulatory axis associated with LUAD prognosis was identified based on the survival-related analysis and differential expression results of RNAs. Although previous studies have extensively reported the role of WT1-AS in different types of cancer, the role of WT1-AS in tumors remains incompletely defined [ 37 , 38 ]. For example, downregulation of WT1-AS can promote the proliferation and invasiveness of gastric cancer cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%